Escape through a time-dependent hole in the doubling map - Livorati, André L. P.; Georgiou, Orestis; Dettmann, Carl P.; Leonel, Edson D. [UNESP] (American Physical Society (APS), 2014)
We investigate the escape dynamics of the doubling map with a time-periodic hole. Ulam's method was used to calculate the escape rate as a function of the control parameters. We consider two cases, oscillating or breathing holes, where the sides of the hole are moving in or out of phase respectively. We find out that the escape rate is well described by the overlap of the hole with its images, for holes centered at periodic orbits. © 2014 American Physical Society.